Validity of a two-distance simplified testing method for determining critical swimming velocity - Rodriguez, F.; Moreno, D.; Keskinen, K. (Biomechanics and Medicine in Swimming IX, 2003)
This study aimed to validate a simplified two-distance testing method for determining vcrit (based on performance times in 100 and 400 m maximal swims) in competitive swimmers. Fifty-one competitive swimmers of national level aged 18-26 years performed a freestyle Aerobic-Anaerobic Standard Swimming Test (Rodríguez 1999) consisting of a two-speed test over 400 m, with 20-min rest, followed by a maximal 100 m swim after one hour rest. Capillary blood samples for lactate analysis were obtained from the earlobe at min 1, 3, 5, 7, and 10 after each test. The average speed corresponding to 4 mmol·L-1 blood lactate (v4) was calculated (Mader et al. 1978). Critical velocity (vcrit) was computed as the slope of the linear regression equation between distance and average speed in 100 and 400 m (v100, v400). The results clearly confirmed the validity of vcrit as a simple, non-invasive -although still controversial- indicator of swimming aerobic endurance (Wakayoshi et al. 1992). The simplified two-distance protocol (all-out 100 and 400 m swims in one testing session) used for determining vcrit compared favorably to other methods requiring a higher number of swims or longer distances, and can be proposed as an equally valid and more feasible procedure.